Method for replacing objects in 4F correlator: testing - Yezhov, P.V.; Kuzmenko, A.V.; Smirnova, Т.N.; Ivanovskyy, A. A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The method of pattern recognition based on replacement of object images incoming to the correlator by object-dependent synthesized phase objects calculated using the iterative Fourier-transform algorithm was developed by us earlier. In this work, we performed experimental testing the above method by using an optical-digital 4F-correlator. Synthesized phase objects were inputed into the correlator through the spatial light modulator LC2002. Holographic matched filters were recorded using self-developing photopolymers PPC-488. For two test objects, we obtained unified (δ-like) correlation signals with the signal-to-noise ratio reaching 24 dB, while the diffraction efficiency of these filters was up to 30%.